2010
DOI: 10.1103/physrevb.81.033402
|View full text |Cite
|
Sign up to set email alerts
|

Strain and coordination effects in the adsorption properties of early transition metals: A density-functional theory study

Abstract: Strain and coordination effects in the adsorption on early transition metals were studied using density functional theory. We show that, in contrast to late transition metals, early transition metal surfaces with a less than half-filled local d-band exhibit lower adsorption energies upon lattice expansion and on low-coordinated sites, in agreement with predictions based on the d-band model. This demonstrates that the d-band model can be extended to early transition metals. Implications of these results for hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
120
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(121 citation statements)
references
References 30 publications
(30 reference statements)
1
120
0
Order By: Relevance
“…Recently, Schnur et al [53] have studied strain and coordination effects in the adsorption on early 3d and 4d transition-metal surfaces (Sc, Ti, V, Cr, and Mn, Zr, Nb) using density functional theory. Their found that except for Mn and Zr, the CO binding to low coordinated sites of all considered early transition metals is weaker than the binding to the high coordinated sites.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Schnur et al [53] have studied strain and coordination effects in the adsorption on early 3d and 4d transition-metal surfaces (Sc, Ti, V, Cr, and Mn, Zr, Nb) using density functional theory. Their found that except for Mn and Zr, the CO binding to low coordinated sites of all considered early transition metals is weaker than the binding to the high coordinated sites.…”
Section: Discussionmentioning
confidence: 99%
“…The tensile strain on late transition metals strengthening the binding is universally accepted. [ 125 ] This understanding is supported by the d-band model where tensile strain narrows the d-band width, causing an upward shift of the d-band, allowing for stronger interaction with adsorbates. [ 126 ] However, the trend, ''tension strengthens binding'', is not always observed in theoretical calculations.…”
Section: Catalytic Properties Of Shape-controlled Nanomaterialsmentioning
confidence: 98%
“…It explains trends in reactivity from one transition metal to the next, and the effects of alloying, structure, strain, defects, and so forth. A large number of calculated and experimental results have been accounted for in this way (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). An example of experimental results explained by the d-band model is included in Fig.…”
Section: Density Functional Theory Calculations Of Surface Chemistrymentioning
confidence: 99%